EFFECT OF METOPROLOL THERAPY ON THE ARTERIAL STIFFNESS - V. E. Oleynikov; I. B. Matrosova; Y. A. Tomashevskaya; L. I. Gusakovskaya; E. A. Melnikova (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate an antihypertensive efficacy and influence on the arterial stiffness of 24-week treatment with metoprolol tartrate in patients with hypertension (HT) degree 1-2. Material and Methods. Patients with HT degree 1-2 (n=38) received therapy with metoprolol tartrate 50-200 mg QD for 24 weeks. Bifunctional daily blood pressure (BP) and electrocardiogramm monitoring with evaluation of central aortic pressure indicators as well as volume sphygmography were performed at baseline and after 24 weeks of therapy. Results. The 24-week  therapy with metoprolol  tartrate was effective  in 47.2% of patients. Significant  improvement  in central aortic pressure  [systolic BP decreased  from 129.8±7.3  to 118.8±7.2 mm Hg; p<0.001; dyastolic BP decreased from 90 (87;93) to 80 (77;84) mm Hg; p<0.001] with the not significant changes of augmentation index (from 18.3±13.2 to 19.5±13.4; p>0.05). Significant reduction in arterial stiffness indexes was revealed with volume sphygmography: CAVI1 from 8.6 (8.1;9.6) to 8.0 (7.3;8.3); p<0.01; L-CAVI1 from 8.9 (7.6;9.9) to 7.9 (7.2;8.5), p<0.001. Conclusion. Metoprolol tartrate is an effective antihypertensive drug that improves the structural and functional properties of arteries.